Novel axially carborane-cage substituted silicon phthalocyanine photosensitizer; synthesis, characterization and photophysicochemical properties - Atmaca, Goknur Yasa; Dizman, Cemil; Eren, Tarik; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The novel axially dicarborane substituted silicon (IV) (SiPc-DC) phthalocyanine was synthesized by treating silicon phthalocyanine dichloride SiPc(Cl)(2) (SiPc) with o-Carborane monool. The compound was characterized by mass spectrometry, UV Vis, FT-IR, H-1 and B-11 Nuclear Magnetic Resonance Spectroscopy (NMR). Spectral, photophysical (fluorescence quantum yield) and photochemical (singlet oxygen (Phi(Delta)) and photodegradation quantum yield (Phi(d))) properties of the complex were reported in different solutions (Dimethyl sulfoxide (DMSO), Dimethylformamide (DMF) and Toluene). The results of spectral measurements showed that both SiPc and carborane cage can have potential to be used as sensitizers in photodynamic therapy (PDT) and boron neutron capture therapy (BNCT) by their singlet oxygen efficiencies (Phi(Delta)= 0.41, 0.39). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Silicon; Carborane; Photochemistry; Photophysic; VITRO PHOTODYNAMIC ACTIVITIES; POLY(ETHYLENE GLYCOL) CHAINS; BOVINE SERUM-ALBUMIN; METAL PHTHALOCYANINES; ZINC PHTHALOCYANINES; COMPLEXATION; AGGREGATION; PDT; Spectroscopy